2021
DOI: 10.15252/embr.202051475
|View full text |Cite
|
Sign up to set email alerts
|

ALIX and ceramide differentially control polarized small extracellular vesicle release from epithelial cells

Abstract: Exosomes, important players in cell-cell communication, are small extracellular vesicles of endocytic origin. Although single cells are known to release various kinds of exosomes (referred to as exosomal heterogeneity), very little is known about the mechanisms by which they are produced and released. Here, we established methods of studying exosomal heterogeneity by using polarized epithelial cells and showed that distinct types of small extracellular vesicles (more specifically CD9-and CD63-positive, Annexin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 38 publications
2
72
0
Order By: Relevance
“…However, the role of the ESCRT complexes in cargo loading and ILV generation for exosome secretion is increasingly challenged by other studies. For example, a recent study has shown that knockdown of individual ESCRT subunits counterintuitively increases exosome secretion by causing lysosomal dysfunction ( Matsui et al, 2021 ). These findings are also in line with studies showing that the lysosomal degradation of several endocytosed receptors requires the ESCRT machinery for proper internalization of these receptors into ILVs ( Futter et al, 1996 ; Haglund et al, 2003 ; Yamashita et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of the ESCRT complexes in cargo loading and ILV generation for exosome secretion is increasingly challenged by other studies. For example, a recent study has shown that knockdown of individual ESCRT subunits counterintuitively increases exosome secretion by causing lysosomal dysfunction ( Matsui et al, 2021 ). These findings are also in line with studies showing that the lysosomal degradation of several endocytosed receptors requires the ESCRT machinery for proper internalization of these receptors into ILVs ( Futter et al, 1996 ; Haglund et al, 2003 ; Yamashita et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…This assay depends on capturing antibodies against three individual tetraspanins, CD63, CD9, CD81 and isotype control mouse IgG and cocktail of all three tetraspanin antibodies conjugated with SULFO-TAG for detection. The geometric mean of the concentrations for three tetraspanins was calculated to better reflect the total yield of NDEV biomarkers for each sample since it is now well-established that different sub-populations of EVs exist with variable tetraspanin expression [27,28]. Essentially, normalization of NDEV biomarkers by the geometric mean of tetraspanins is used to express their levels per standardized unit of EV content for each sample (conceptually equivalent to expressing the measured concentration of each biomarker per recovered EV).…”
Section: Biomarker Measurementsmentioning
confidence: 99%
“…These two types of exosomes show distinct differences in their size and protein composition [19]. Interestingly, Matsui et al showed two independent mechanisms for exosome release across the apical and basolateral plasma membranes [20]. This group showed that ceramide plays an essential role in basolateral exosome release whereas, ALIX is important for apical exosome release [20].…”
Section: Regulation Of Size Distributionmentioning
confidence: 99%